Role of Kidney Biopsy in Patients with Lupus Nephritis – A Review - Asha Patil, Nikhitha Shetty, Shankar Prasad Nagaraju (International Journal of Advanced Science and Technology, 2020)
Introduction: Lupus nephritis is lupus evidence of systemic lupus erythematosus. A kidney biopsy is considered a gold standard procedure to assess the disease activity in patients with lupus nephritis. This study aims to evaluate the importance of repeat renal biopsy in lupus nephritis patients.Method: We conducted a review using relevant keywords and databases (PubMed, Web of Science, Scopus, CINAHL, and Cochrane) to find the importance of kidney biopsy in Lupus nephritis patients.Result: A total of 43 articles were selected, 23 articles included for the review on abstract analysis for similar studies, and availability of the full texts. Finally, 07 articles included in the review. The studies showed mixed results on the decision of kidney biopsy for diagnosis and prognosis in lupus nephritis.Conclusion: First or repeat biopsies depends upon the diagnostic relevance and clinical condition of the patient though there are complications during the procedure.